1984
DOI: 10.1128/jcm.20.5.966-971.1984
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an unclassified Mycobacterium species isolated from patients with Crohn's disease

Abstract: The characteristics of an unclassified Mycobacterium sp. isolated from three patients with Crohn's disease are presented. The organism is extremely fastidious and mycobactin dependent and may require up to 18 months of incubation for primary isolation. Colony morphology is rough. Characteristics are unlike those of any presently defined species. The isolates produced positive niacin, catalase, and 2-week arylsulfatase reactions and were susceptible to neotetrazolium chloride (1:40,000), streptomycin (2 ,ug/ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
6

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(110 citation statements)
references
References 18 publications
2
102
0
6
Order By: Relevance
“…54 The disease becomes evident after a latent period of several years. 53 Failure to isolate mycobacteria from humans with Crohn's disease does not disprove mycobacteria as the cause, because the organism is difficult to isolate. Mycobacteria are often not found in humans with disease known to be caused by the organism, and mycobacterial infections in humans are not always serologically detectable.…”
Section: Etiopathogenesis Of Gementioning
confidence: 99%
“…54 The disease becomes evident after a latent period of several years. 53 Failure to isolate mycobacteria from humans with Crohn's disease does not disprove mycobacteria as the cause, because the organism is difficult to isolate. Mycobacteria are often not found in humans with disease known to be caused by the organism, and mycobacterial infections in humans are not always serologically detectable.…”
Section: Etiopathogenesis Of Gementioning
confidence: 99%
“…Conflicting results have been reported concerning M. paratuberculosis (Gaya et al, 2004;Huggett et al, 2004). Some authors showed that these bacteria can be isolated from tissues of patients with CD (Chiodini et al, 1984), but studies using immunohistochemistry detection or polymerase chain reaction techniques disagree over its aetiological role (Sanderson et al, 1992;Dell'Isola et al, 1994;Rowbotham et al, 1995). The identification of Mycobacterium avium ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Crohn's disease (CD) and ulcerative colitis (UC) is still unknown [1]. However, experimental support for the early hypothesis that bacteria or their products might be involved in disease pathogenesis [2,3] has been presented by a large number of studies, which either searched to define a single pathogenetic bacterium causing the disease [4][5][6] or investigated the possibility that intestinal inflammation results from hyperresponsiveness to ubiquitous bacterial antigens or products of the resident intestinal flora [7,8]. Although there is to date no convincing evidence for the aetiological involvement of any defined microbial species in IBD, this is still an area of active research and, as in a recent report providing immunohistochemical evidence for a role for Listeria species (spp.…”
Section: Introductionmentioning
confidence: 99%